Molecular Characterization of Alkaline Protease Gene Isolated from Aeromonas hydrophila strain AH10 - Babu, N.G. Ramesh; Aji, Anupa Mary (International Journal of Applied Sciences and Biotechnology, 2020)
Alkaline protease enzymes are enzymes which can catalyze the process of proteolysis between the pH ranges from 8 to 12. Extracellular alkaline proteases are used as additives in detergent powders. In the present study, source of the organism was from a detergent contaminated area. The study has been carried out in Aeromonas hydrophila AH10 strain that produces protease enzyme with an alkaline pH optimum. The organism was a gram-negative rod with a protease enzyme activity of 0.385 ml/min. purification of the protease enzyme from the bacteria was carried out. This protease is suitable for use in alkaline detergent powders as well as in silver recovery process. The Aeromonas hydrophila strain AH10 gene encoding this high-alkaline protease was cloned and characterized. Int. J. Appl. Sci. Biotechnol. Vol 8(2): 154-160